DECREASED URINARY LEVELS OF SIRT1 AS NON-INVASIVE BIOMARKER OF EARLY RENAL DAMAGE IN HYPERTENSION. (June 2022) - Martinez-Arroyo, Olga; Ortega, Ana; Solaz, Elena; Martinez, Fernando; Martinez-Hervas, Sergio; Redon, Josep; Cortes, Raquel
Abstract : Objective: Hypertension and diabetes mellitus (DM) produce renal injury. Sirtuins have become important players in renal damage, but their value as biomarkers is poorly assessed. The aims of the study were to evaluate the sirtuin1 levels (SIRT1), and miRNAs miR-34a and miR-200, that regulate SIRT1 expression in urinary cell pellet from hypertensive patients with incipient renal damage with and without diabetes. In addition, to mimic disease conditions and deepen into the implications of SIRT1 in podocyte injury, employed cultured podocytes subjected to high glucose (HG) and angiotensin II (Ang II) concentrations. Design and method: We quantified urinary SIRT1 and claudin 1 (CLDN1) mRNA and miR-34a and miR-200a levels by quantitative real-time polymerase chain reaction (RT-qPCR) from urinary cell free pellet from patients and in cultured human immortalized podocytes treated with HG and ANG II. Protein levels and subcellular localization were analyzed by Western blot and fluorescence analyses by confocal microscopy. Results: We found decreased SIRT1 levels in patients with increased urinary albumin excretion (UAE), the lowest with diabetes presence, and a strong association with UAE, discriminating incipient renal damage. In vitro experiments also showed SIRT1 overall decreases in podocyte cultures under treatment conditions. In urine samples, miR-34a was reduced and miR-200a increased, both related to UAE levels. However, both miRNAs were generally increased in podocyte cultures under high glucose and angiotensin-II treatment. Conclusions: Results evidenced reduction of urinary SIRT1 from hypertensives with or without DM. The decrease of SIRT1 and increase of CLDN1 in patients and podocytes subjected to stress support the implication of both in renal injury and evidence a reflection in urinary levels. The alterations found in miR-34a and miR-200a both in patients' urine and podocyte cultures reveal novel points to further address their implication in renal injury through SIRT1 regulation. Interestingly, SIRT1 mRNA levels and miR-200a are related to increases in UAE and discriminate the presence of UAE in patients. In summary, SIRT1 mRNA measurements is an easily accessible and non-invasive method to early characterize renal damage in patients.